Penguatan Tata Kelola Rumah Qur’an melalui Pengembangan Website, Dashboard Hafalan Santri, dan Konten Digital - Aminah Dewi Rahmawati; Arik Kurniawati; Puji Rahayu Ningsih; Indah Cahyani; Hilman Dafiq; Dhani Syafreal; Septia Nur Fadhilah (Jurnal Pengabdian Masyarakat Charitas, 2025)
This community empowerment program enhances administrative management at Asy-Syafi'i Rumah Qur'an in Bangkalan through the adoption of a digital system and social media–based promotional strategies. The center previously relied on manual student data recording, non-digital memorization monitoring, and had limited reach in sharing information about its activities. The program consisted of needs assessment, design of a web-based platform and memorization dashboard, system training, and training on digital content creation. The implementation of the new system improved administrative efficiency, data accuracy, and monitoring processes, while the digital content training strengthened the center’s self-promotion capabilities. Overall, the program supports better management, transparency, and sustainability for community-based Qur'an learning centers in the digital era.